Relationship Of Limb Muscle Strength And Concentration With Extraculular Futsal Shooting Results At 1 Rupat State Junior High School: Hubungan Kekuatan Otot Tungkai Dan Konsentrasi Dengan Hasil Shooting Futsal Ekstrakulikuler Di SMP Negeri 1 Rupat - Muhammad Azwan; Oki Candra (Badnur Medisa Group, 2022)
The purpose of this study was to determine the relationship between leg muscle strength and concentration with the results of extracurricular Futsal shooting at SMPN 1 Rupat. This research is a correlational study. The population of this study were futsal extracurricular students at SMP Negeri 1 Rupat. The sample in this study were all futsal extracurricular students of SMP Negeri 1 Rupat, totaling 20 people. The instrument of this study was to obtain data on leg muscle strength using the leg and back dynamometer test, then the athlete's concentration was taken by means of tests and measurements using the Grid ConcentrationTest instrument and also a test of the implementation of shooting results for futsal players. Data analysis on the contribution of eye and hand coordination to the long jump ability using the